Perizinan Lingkungan Terintegrasi Pasca Berlakunya Undang-Undang Cipta Kerja - Ubaiyana .; Kristina Viri (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2022)
Indonesia doesn’t clearly regulate, adheres to an integrated environmental licensing system or not. Thisresearch focuses on three problems, namely examining in depth the concept of integrated permits and their urgency and analyzing integrated environmental permits before and after UUCK. This study aims to examine in depth the concept of an integrated environmental permit which then becomes a benchmark in analyzing environmental permits adopted by Indonesian law before and after the enactment of the UUCK. This type of research is normative legal research with a statutory approach, a historical approach, and a conceptual approach. This research material is sourced from primary legal materials and secondary legal materials, with data collection techniques using library methods which are then analyzed using descriptive and deductive-inductive methods. The results showed that in the implementation before the enactment of the UUCK, namely the regime of the Environmental Protection and Management Act (UUPPLH), there were already several permits that were integrated with environmental permits. Meanwhile, after the enactment of UUCK, UUCK replaced environmental permits with environmental approvals. This change has the potential to sacrifice environmental sustainability and has the consequence of eliminating the integration of environmental permits with other permits previously applicable in UUPPLH.